2011
DOI: 10.1021/ef2008908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure Characterization, and Engine Performance Test of Ethylene Glycol n-Propyl Ether Palm Oil Monoester as Biodiesel

Abstract: In this paper, ethylene glycol n-propyl ether palm oil monoester (EGPEPOM) was synthesized through transesterification of refined palm oil and ethylene glycol n-propyl ether with sodium as the catalyst. Its chemical structure was characterized through Fourier transform infrared (FTIR) spectrometry, hydrogen atom nuclear magnetic resonance (1H NMR), and gel permeation chromatography (GPC) analyses. To investigate the engine performance of EGPEPOM, tests on a two-cylinder direct-injection (DI) diesel engine were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Meanwhile ethylene glycol ethyl ether and propyl ether types biodiesels and diethylene glycol and triethylene glycol monomethyl ether types of biodiesels were developed to understand their effects. Table 1 lists some of new types of biodiesels and their fuel properties our group developed in recent years [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The new types of biodiesels have a CN around 70, oxygen content about 17%, which are higher than FAME.…”
Section: Biodiesel Fuel Propertiesmentioning
confidence: 99%
“…Meanwhile ethylene glycol ethyl ether and propyl ether types biodiesels and diethylene glycol and triethylene glycol monomethyl ether types of biodiesels were developed to understand their effects. Table 1 lists some of new types of biodiesels and their fuel properties our group developed in recent years [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The new types of biodiesels have a CN around 70, oxygen content about 17%, which are higher than FAME.…”
Section: Biodiesel Fuel Propertiesmentioning
confidence: 99%
“…A variety of chromatographic and spectroscopic techniques are used to assess the quality of biodiesel, including thin layer chromatography, , gas chromatography with flame ionization detector (GC-FID), gas chromatography–mass spectrometry, headspace-based gas chromatography, gas chromatography-differential mobility spectrometry with cluster analysis, high-performance liquid chromatography, gel permeation chromatography, supercritical fluid chromatography, near-infrared spectroscopy, , Fourier-transform spectroscopy, , Raman spectroscopy, 13 C NMR, H NMR, and sequential/flow injection analysis (SIA/FIA). , …”
Section: Introductionmentioning
confidence: 99%
“…Gao et al . developed ethylene glycol n ‐propyl ether palm oil monoester as a biodiesel and studied its combustion performances and emissions characteristics. It was observed that not only were such pollutants as smoke, CO and unburned HC substantially reduced but also NOx emissions were lowered in the tests.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high oxygen content of the biofuel, the engine thermal efficiency was remarkably improved, however, both the peak of heat release rate and the peak of in-cylinder pressure decreased owing to its low lower heating value. Gao et al [19] developed ethylene glycol n-propyl ether palm oil monoester as a biodiesel and studied its combustion performances and emissions characteristics. It was observed that not only were such pollutants as smoke, CO and unburned HC substantially reduced but also NOx emissions were lowered in the tests.…”
mentioning
confidence: 99%